An Analysis of Students’ Speaking Anxiety in English Classroom at SMAN 2 Siak Hulu - Najiha Najiha; Betty Sailun (Lectura : Jurnal Pendidikan, 2021)
Many foreign language students are apprehensive about learning a new language in a certain situation. When they are asked to express their thoughts in front of their peers and lecturers, they appear to become more anxious. Then, when they talk in English, they never feel completely at ease. Consequently, the aim of this research is to determine the level of student speaking anxiety and to determine the dominant type of anxiety that occurs in English classroom. This research was conducted by using descriptive quantitative study. The research participants were the third-grade students of SMAN 2 Siak Hulu of academic year 2020/2021. The total of students was 34 students. Then, the researchers obtained the data through questionnaires. The result of this research showed that most experienced level of speaking anxiety in the third-grade students was Mildly Anxious. Additionally, based on FLCAS, there are 3 types of speaking anxiety students experienced in the classroom was negative evaluation, followed by test anxiety and communication apprehension. In this case, the researchers found that “Communication Apprehension” was the main factor causing around 27 (79%) students to feel nervous, followed by 23 (68% students with “Fear of Negative Evaluation” factors, and the lowest factor for 22 (65%) students was “Test Anxiety”. Therefore, the third-grade students of SMAN2 Siak Hulu were categorized at the Mildly Anxious level of speaking anxiety in the English classroom.